2020
DOI: 10.1089/jayao.2019.0140
|View full text |Cite
|
Sign up to set email alerts
|

Reaching Adolescent and Young Adult Cancer Patients Through Social Media: Impact of the Photographs of Meaning Program

Abstract: This study assessed the feasibility and preliminary efficacy of the Photographs of Meaning Program for Adolescent and Young Adult cancer patients and survivors (POM-AYA). Methods: POM-AYA is a structured 10-week meaning-based intervention in which participants post photographs and accompanying narratives through a social media platform. Measures of depression, overall quality of life (QoL), and spiritual well-being were assessed on consent (T1), after completing the 10-week intervention (T2) and 2 months' post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…Samples sizes ranged from small pilot trials ( n = 10) to larger scale randomized controlled trials ( n = 136). Most studies recruited young people diagnosed with a mental health condition by a clinician or who scored above a clinical threshold on valid clinical measure ( Alvarez-Jimenez et al, 2020 , Alvarez-Jimenez et al, 2018 ; Bailey et al, 2020 ; Ludwig et al, 2021 ; McEnery et al, 2021 ; Rice et al, 2020 , Rice et al, 2018 ), with others focused on young people with self-reported mental health conditions ( Karim et al, 2021 ; Radovic et al, 2018 ; Watkins et al, 2020 ), a cancer diagnosis ( Greer et al, 2019 ; Pailler et al, 2020 ), and college students ( Asbury et al, 2018 ; Frith and Loprinzi, 2017 ; Yu, 2020 ). The most common study design was non-randomized pre-post trial.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Samples sizes ranged from small pilot trials ( n = 10) to larger scale randomized controlled trials ( n = 136). Most studies recruited young people diagnosed with a mental health condition by a clinician or who scored above a clinical threshold on valid clinical measure ( Alvarez-Jimenez et al, 2020 , Alvarez-Jimenez et al, 2018 ; Bailey et al, 2020 ; Ludwig et al, 2021 ; McEnery et al, 2021 ; Rice et al, 2020 , Rice et al, 2018 ), with others focused on young people with self-reported mental health conditions ( Karim et al, 2021 ; Radovic et al, 2018 ; Watkins et al, 2020 ), a cancer diagnosis ( Greer et al, 2019 ; Pailler et al, 2020 ), and college students ( Asbury et al, 2018 ; Frith and Loprinzi, 2017 ; Yu, 2020 ). The most common study design was non-randomized pre-post trial.…”
Section: Resultsmentioning
confidence: 99%
“… • Significant effects at follow-up for happiness in both groups (p = .02; p = .04). Pailler et al, 2020 10 weeks Meaning-based intervention adapted from a manualized meaning-centered psychotherapy intervention. Aimed to help cancer patients sustain and enhance a sense of meaning, purpose, and peace through facilitating social sharing, narrative, and creativity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AYA survivors of cancer cite the importance of recreational video game use in both creating/maintaining social connection and distraction from reality 6 . Digital technologies have long been utilized for psychosocial intervention delivery, especially for skill development or education about a diagnosis 7–12 . However, the world of digital technologies is rapidly evolving; frequent change complicates how these platforms may be used for research or clinical care 13 .…”
Section: Introductionmentioning
confidence: 99%
“…There is also a need to identify the downsides of peer support among individuals with cancer to generate possible solutions, as social media use can negatively influence well-being among young adults [ 35 ]. Previous studies have often focused on the positive impacts of social media use, with a limited focus on potential downsides in these novel approaches [ 29 , 36 ]. If it is known that emotions drive social connections on the web, including negative mental experiences (eg, isolation and fear) [ 30 ], then there is a need to provide more balanced approaches to understand why young adults are motivated to organically share their stories and drawbacks of peer support.…”
Section: Introductionmentioning
confidence: 99%